Career development of expert coaches - Nash, C. S.; Sproule, J. (International Journal of Sports Science and Coaching, 2009)
Careers in coaching are a relatively new phenomenon in the UK and at present appear to be limited to the performance coach. This study, using an interview approach, examined the transition of expert coaches (n = 9) through various stages in their careers. The main aim of this study was to ascertain if expert coaches could explain the process of their development to perceived expert status. The interviewed coaches could offer no real insight into their designation as experts. They did raise some questions regarding the value of current coach education provision, especially as it related to their current role as coaches of elite athletes. Their methods of development were considered to be informal, with networking with other coaches of like mind believed to be essential to their progress. The ability to contextualise knowledge and information to suit both the individual and situation, as well as appropriate mentors at the initial stages of their coaching careers were also regarded as vital.